Enhancement of extraction efficiency and functional properties of chickpea protein isolate using pulsed electric field combined with ultrasound treatment - Xin-Jue Lai; Jian-Quan Chen; Jing Nie; Pei-Feng Guo; Muhammad Faisal Manzoor; Yan-Yan Huang; Jian Li; Song-Yi Lin; Xin-An Zeng; Rui Wang (Ultrasonics Sonochemistry)
Chickpea protein isolate (CPI) is a promising dietary protein with the advantages of low allergenicity, easy digestion and balanced composition of essential amino acids. However, due to the thick skin of chickpeas, the extraction of CPI is challenging, resulting in lower efficiency of the alkaline extraction-isoelectric precipitation (AE-IEP) method. Therefore, the present study investigated the effect of pulsed electric field combined with ultrasound (PEF-US) treatment on the extraction efficiency of CPI and the functional properties was characterized. Parameter optimization was carried out using response surface methodology (RSM), with the following optimized conditions: pulse duration of 87 s, electric field intensity of 0.9 kV/cm, ultrasonic time of 15 min, and ultrasonic power of 325 W. Under the optimized conditions, the yield of CPI after combined (PEF-US) treatment was 13.52 ± 0.13 %, which was a 47.28 % improvement over the AE-IEP method. This yield was better than that obtained with either individual PEF or US treatment. Additionally, the functional properties (solubility, emulsification, and foaming) of CPI were significantly enhanced compared to AE-IEP. However, the stability of emulsification and foaming did not show significant differences among the four methods. The PEF-US method efficiently extracts CPI with excellent functional properties, enabling the production of proteins as desired functional additives in the food industry.